The MANGUA Project: A Population-Based HIV Cohort in Guatemala. (6th September 2015) - García, Juan Ignacio; Samayoa, Blanca; Sabidó, Meritxell; Prieto, Luis Alberto; Nikiforov, Mikhail; Pinzón, Rodolfo; Santa Marina de León, Luis Roberto; Ortiz, José Fernando; Ponce, Ernesto; Mejía, Carlos Rodolfo; Arathoon, Eduardo; Casabona, Jordi; et al.
Abstract : Introduction. The MANGUA cohort is an ongoing multicenter, observational study of people living with HIV/AIDS in Guatemala. The cohort is based on the MANGUA application which is an electronic database to capture essential data from the medical records of HIV patients in care. Methods. The cohort enrolls HIV-positive adults ≥16 years of age. A predefined set of sociodemographic, behavioral, clinical, and laboratory data are registered at entry to the cohort study. Results. As of October 1st, 2012, 21 697 patients had been included in the MANGUA cohort (median age: 33 years, 40.3% female). At enrollment 74.1% had signs of advanced HIV infection and only 56.3% had baseline CD4 cell counts. In the first 12 months after starting antiretroviral treatment 26.9% (n = 3938 ) of the patients were lost to the program. Conclusions. The implementation of a cohort of HIV-positive patients in care in Guatemala is feasible and has provided national HIV indicators to monitor and evaluate the HIV epidemic. The identified percentages of late presenters and high rates of LTFU will help the Ministry to target their current efforts in improving access to diagnosis and care.